3D Honeycomb Architecture Enables a High‐Rate and Long‐Life Iron (III) Fluoride–Lithium Battery. Issue 43 (12th September 2019) - Wu, Feixiang; Srot, Vesna; Chen, Shuangqiang; Lorger, Simon; van Aken, Peter A.; Maier, Joachim; Yu, Yan
Abstract: Metal fluoride–lithium batteries with potentially high energy densities, even higher than lithium–sulfur batteries, are viewed as very promising candidates for next‐generation lightweight and low‐cost rechargeable batteries. However, so far, metal fluoride cathodes have suffered from poor electronic conductivity, sluggish reaction kinetics and side reactions causing high voltage hysteresis, poor rate capability, and rapid capacity degradation upon cycling. Herein, it is reported that an FeF3 @C composite having a 3D honeycomb architecture synthesized by a simple method may overcome these issues. The FeF3 nanoparticles (10–50 nm) are uniformly embedded in the 3D honeycomb carbon framework where the honeycomb walls and hexagonal‐like channels provide sufficient pathways for the fast electron and Li‐ion diffusion, respectively. As a result, the as‐produced 3D honeycomb FeF3 @C composite cathodes even with high areal FeF3 loadings of 2.2 and 5.3 mg cm −2 offer unprecedented rate capability up to 100 C and remarkable cycle stability within 1000 cycles, displaying capacity retentions of 95%–100% within 200 cycles at various C rates, and ≈85% at 2C within 1000 cycles. The reported results demonstrate that the 3D honeycomb architecture is a powerful composite design for conversion‐type metal fluorides to achieve excellent electrochemical performance in metal fluoride–lithium batteries. Abstract : FeF3 nanoparticles (10–50 nm) are uniformly embedded in a 3D honeycomb architecture where the honeycomb walls and hexagonal‐like channels provide sufficient pathways for fast electron and Li‐ion diffusion, respectively. As a result, the as‐produced 3D honeycomb FeF3 @C composite cathodes offer unprecedented rate capability up to 100C and remarkable cycle stability within 1000 cycles.